2018
DOI: 10.1016/j.bbmt.2017.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transplant Cyclophosphamide as Sole Graft-versus-Host Disease Prophylaxis Is Feasible in Patients Undergoing Peripheral Blood Stem Cell Transplantation for Severe Aplastic Anemia Using Matched Sibling Donors

Abstract: High-dose cyclophosphamide (PTCY) after allogeneic hematopoietic cell transplantation (HSCT) has been shown to be effective in preventing graft-versus-host disease (GVHD) after HLA-matched bone marrow transplantation. We performed a phase II study of PTCY given at 50 mg/kg i.v. on days 3 and 4 as the sole GVHD prophylaxis after HSCT for severe aplastic anemia (SAA) in patients receiving granulocyte colony-stimulating factor-mobilized peripheral blood stem cell (PBSC) grafts from HLA-matched related donors afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…In the present study, in both the URD and MSD groups, all patients received 10.0 mg/kg ATG, which may have contributed to the high incidence of CMV viremia. Moreover, the PCR cutoff for positive CMV viremia was 500 copies/mL, lower than the cutoff in a previous study (1000 copies/mL) [46], and this low cutoff may also be an important contributing factor in the high rate of CMV viremia in our institution [47].…”
Section: Discussioncontrasting
confidence: 69%
“…In the present study, in both the URD and MSD groups, all patients received 10.0 mg/kg ATG, which may have contributed to the high incidence of CMV viremia. Moreover, the PCR cutoff for positive CMV viremia was 500 copies/mL, lower than the cutoff in a previous study (1000 copies/mL) [46], and this low cutoff may also be an important contributing factor in the high rate of CMV viremia in our institution [47].…”
Section: Discussioncontrasting
confidence: 69%
“…Post‐transplant cyclophosphamide (PTCy) for GVHD prophylaxis in the setting of matched related (MRD), matched and mismatched unrelated (MUD and MMUD), and haplo‐identical (HI) transplants has been associated with low rates of acute and chronic GVHD . Similarly, ATG has been used extensively for GVHD prophylaxis for MUD transplants with beneficial effects in reducing acute and chronic GVHD .…”
Section: Introductionmentioning
confidence: 99%
“…In up to date transplant practice, multiple agents in combination are typically used for GVHD prophylaxis either with or without PTCy (31) and T cell depleting serotherapy. Recent publications have also demonstrated that single agent PTCy can be effective as GVHD prophylaxis in pediatric and adult cohorts with non-malignant and malignant indications for HSCT (32, 33).…”
Section: Discussionmentioning
confidence: 99%